Apamin structure and pharmacology revisited - Kuzmenkov, Alexey I.; Peigneur, Steve; Nasburg, Joshua A.; Mineev, Konstantin S.; Nikolaev, Maxim V.; Pinheiro-Junior, Ernesto Lopes; Arseniev, Alexander S.; Wulff, Heike; Tytgat, Jan; Vassilevski, Alexander A. (Frontiers in Pharmacology, 2022)
Apamin is often cited as one of the few substances selectively acting on small-conductance Ca2+-activated potassium channels (KCa2). However, published pharmacological and structural data remain controversial. Here, we investigated the molecular pharmacology of apamin by two-electrode voltage-clamp in Xenopus laevis oocytes and patch-clamp in HEK293, COS7, and CHO cells expressing the studied ion channels, as well as in isolated rat brain neurons. The microtitre broth dilution method was used for antimicrobial activity screening. The spatial structure of apamin in aqueous solution was determined by NMR spectroscopy. We tested apamin against 42 ion channels (KCa, KV, NaV, nAChR, ASIC, and others) and confirmed its unique selectivity to KCa2 channels. No antimicrobial activity was detected for apamin against Gram-positive or Gram-negative bacteria. The NMR solution structure of apamin was deposited in the Protein Data Bank. The results presented here demonstrate that apamin is a selective subnanomolar-affinity KCa2 blocker with no significant effects on other molecular targets. The spatial structure as well as ample functional data provided here support the use of apamin as a KCa2-selective pharmacological tool and as a template for drug design.